2013
DOI: 10.1016/j.bbamem.2013.05.022
|View full text |Cite
|
Sign up to set email alerts
|

The transmembrane domain of the T4SS coupling protein TrwB and its role in protein–protein interactions

Abstract: Bacteria use type IV secretion systems to transfer genetic material and proteins from donor to recipient cells, using proteins encoded by conjugative plasmids. Among those proteins the so-called Type IV Coupling Protein plays a central role in the process. One of the best studied members of this family is TrwB, the conjugative coupling protein of R388 plasmid. Previous studies indicated that the transmembrane domain of TrwB plays a role beyond the mere anchoring of the protein to the membrane. TrwB has also be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 57 publications
0
20
0
2
Order By: Relevance
“…Therefore, none of the pilus subunits or TrwD /VirB11 are essential for the stability of the T4SS 3‐10+D4 complex. However, deletion of TrwM /VirB3 or TrwK /VirB4 results in the purification of a complex composed of the core OMC components, TrwH /VirB7 , TrwF /VirB9 and TrwE /VirB10 , as well as TrwB /VirD4 , indicating that TrwB /VirD4 interacts directly with the core complex, presumably through interaction with the N‐terminus of TrwE /VirB10 (Llosa et al , 2003; Segura et al , 2013). Similarly, when pulling the complex using the Δ trwG /virB8 construct, apart from TrwH /VirB7 , TrwF /VirB9 , TrwE /VirB10 and TrwB /VirD4 , only traces of TrwK /VirB4 and its degradation products can be detected, indicating that TrwG /VirB8 serves to stabilize TrwK /VirB4 within the IMC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, none of the pilus subunits or TrwD /VirB11 are essential for the stability of the T4SS 3‐10+D4 complex. However, deletion of TrwM /VirB3 or TrwK /VirB4 results in the purification of a complex composed of the core OMC components, TrwH /VirB7 , TrwF /VirB9 and TrwE /VirB10 , as well as TrwB /VirD4 , indicating that TrwB /VirD4 interacts directly with the core complex, presumably through interaction with the N‐terminus of TrwE /VirB10 (Llosa et al , 2003; Segura et al , 2013). Similarly, when pulling the complex using the Δ trwG /virB8 construct, apart from TrwH /VirB7 , TrwF /VirB9 , TrwE /VirB10 and TrwB /VirD4 , only traces of TrwK /VirB4 and its degradation products can be detected, indicating that TrwG /VirB8 serves to stabilize TrwK /VirB4 within the IMC.…”
Section: Resultsmentioning
confidence: 99%
“…All three ATPases interact with one another and these interactions likely direct the two processes in which T4S systems are involved: pilus biogenesis and substrate secretion (Atmakuri et al , 2004; Ripoll‐Rozada et al , 2013). VirD4 also interacts with the N‐terminally located transmembrane helices of VirB10 (Llosa et al , 2003; Ripoll‐Rozada et al , 2013; Segura et al , 2013). Although the general organization of the conjugative T4S system is well known, the details of the substrate secretion mechanism are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The biological relevance of these findings remains to be evaluated, but it should be noted that several studies have identified functions of the various T4CP domains that could contribute-directly or indirectly-to substrate binding. The NTDs, for example, are unlikely to directly bind substrates, but studies have identified several NTD functions, including binding interactions with other channel subunits, stimulatory effects on T4CP oligomerization and catalytic activity, and contributions to T4CP spatial positioning in the cell (17,(64)(65)(66)(67), that could indirectly affect substrate docking. By virtue of their possible accessibility to secretion substrates in the cytoplasm, the NBDs and CTDs might coordinate with the AAD to recruit substrates through direct substrate engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, a massive 3.2-MDa substructure, comprised of nearly the entire plasmid R388 conjugation system, presented as two distinct subassemblies, the outer-membrane-associated core complex (also termed the outer membrane complex [OMC]) and an even larger inner membrane complex (IMC) (13). The T4CP of this system, TrwB, was not part of this large structure, but several lines of genetic and biochemical evidence suggest it associates with the IMC through a combination of N-terminal transmembrane domain (NTD) and extramembranous contacts (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…There is some evidence for T4CP interactions with VirB10-like subunits of the core complex, and the interaction surfaces generally map within the N-terminal regions of both subunits [96]. Results of two-hybrid studies and mutational analyses have pointed to a contribution of the transmembrane helices of both subunits to this interaction [97]. In A. tumefaciens , however, the transmembrane domain (TMD) of VirB10 can be substituted with heterologous TM domains, including a nondimerizing poly-Leu/Ala helix, without loss of channel function, and further mutational analyses implicated the N-terminal periplasmic loop of VirD4 and both cytoplasmic and periplasmic domains of VirB10 in this interaction [98100].…”
Section: The T4cp Substrate Receptormentioning
confidence: 99%